What Ibn Hisham described as anomalous and rare in his book Ashth al-Masalik to Alfiya Ibn Malik (Journal of the College of Basic Education, 2023)
Summary of the research:This research revolves around the issue of the abnormal and rare in the book “Awdhah Al-Masalak to Al-Fiyat Ibn Malik” by Ibn Hisham, which is one of the books that has a great advantage in explaining Al-Alfiya because of the many opinions it contained and the differences between the two schools of visual and Kufic in many grammatical issues, so we find that there are some poetic evidences that do not respond For the rule and the grammatical law, the grammarians called it terms that indicate its departure from the grammatical rule (such as abnormal, rare, few, etc.). In this research, I traced every word (extraordinary and rare) in the book “Awdhat Al-Masalak”, and mentioned it as it was mentioned by Ibn Hisham, making a title for the grammatical issue in which the word “extraordinary” and “rare” was mentioned and their morphological inflections. search . In the first topic, I dealt with the meaning of anomaly linguistically and idiomatically, then I moved to the word (the abnormal) and its conjugations in a book that explained the paths according to the issues in which the word was mentioned. Following the same approach in the word that preceded it